Anchorage Loss Comparison in 0.022 and 0.018 Self Ligating Bracket Systems after Closing of Extraction Spaces with Sliding Mechanics (Orthodontic Journal of Nepal, 2025)
Introduction: Anchorage is the resistance to unwanted orthodontic tooth movement and anchorage loss in orthodontics can be detrimental to treatment, an unfortunate result of various treatment procedures. This study aimed to evaluate the anchorage loss from preretraction to postretraction with sliding mechanics. This retrospective clinical study compared 0.022 and 0.018 self-ligating MBT bracket systems.Materials and Methods: Based on the bracket slot size, a total of 28 patients were retrospectively divided into two groups of 14 patients each. Self-ligating (0.022” slot), mean age 19.14 ± 2.12 years designated as Group I and self-ligating (0.018”slot) mean age 19.71 ± 1.80 years designated as Group II . At two intervals of time, T1: Preretraction and T2: Postretraction and space closure, standard study models were prepared. Anchorage loss in terms of maxillary and mandibular molar mesial migration, intercanine width, intermolar width and space closure was evaluated from preretraction and post space closure study models. To evaluate data, SPSS statistical programme 19.0 Version was used and to compare differences in mean scores between the two independent groups independent t test was utilized.Results: The mean value of anchorage loss for maxillary arch in Gr I was 0.68±0.20mm (1.93%) & in Gr II it was 0.73±1.38mm (2.13%) with the p-value of 0.573. For mandibular arch the mean value of anchorage loss in Gr I was 0.28±0.20mm (0.63%) & in Gr II it was 0.33±0.38 mm (0.83%), p-value 0.273. The findings of this research were that from T1 to T2, there was no significant substantial variation in anchorage loss between the two groups.Conclusion: From preretraction to postretraction using sliding mechanics, no statistically significant difference was found in anchorage loss between 0.022 & 0.018 inch self-ligating bracket systems.